Rapid and efficient carbon dioxide capture through benzene-1,4-diamine based hierarchical porous hyper-cross-linked polymers - Areej, Isham; Raza, Saqlain; Khalid, Rimsha; Ashraf, Faiza; Abid, Muhammad Amin; Izan Izwan, Misnon; Tan, Bien (Elsevier B.V., 2025)
Carbon dioxide (CO2) emission causes global warming which has been the greatest challenge for humanity since last decade. Herein, we developed nitrogen and phosphorus rich hyper cross-linked polymers for CO2 capture, designated as BDA-HCP-1 and BDA-HCP-2 (benzene-1,4-diamine based hyper cross-linked polymers) having BET surface area 294.5904 m2g-1 and 519.6918 m2g-1 respectively. The pore width range of BDA-HCP-1 and BDA-HCP-2 is 0–25 nm and 0–15 nm and pore volume of BDA-HCP-1 and BDA-HCP-2 is 0.01–0.18cm3/g and 0.01–0.25 cm3/g, respectively.Total pore volume, studied using DFT, is 0.20100 cm3/g for BDA-HCP-1 and 0.27973 cm3/g for BDA-HCP-2. BJH cumulative pore volume of BDA-HCP-1 is 0.113023 cm3/g and BDA-HCP-2 is 0.284733 cm3/g. The BDA-HCP-1and BDA-HCP-2 were synthesized by replacement of chlorines of hexachlorocyclophosphazenes (HCCP) and phosphorousdichlorophosphazenes (PDCP) with bezene-1,4-diamine to form linear and cyclic polyphosphazenes, which are later cross-linked through Friedal crafts reaction to form hyper cross-linked polymers. The maximum CO2 adsorption quantity of BDA-HCP-1 is 48.62 cm3/g (CO2 weight adsorbed 9.070 % with equilibrium time 8.16 min) at 273K/1 bar and 37.96 cm3/g (weight adsorbed 7.15 % with equilibrium time 8.25 min) at 298K/1 bar that gives adsorption capacity of 2.14 mmol/g and 1.69 mmol/g, respectively. Adsorption capacity of BDA-HCP-2 is 2.30 mmol/g and 2.13 mmol/g at 273 K/1 bar and 298 K/1 bar respectively. It is calculated from maximum CO2 adsorption quantity of 51.6 cm3/g (weight adsorbed 9.83 % with equilibrium time 11.4 min, at 273 K/1 bar) and 47.7 cm3/g (weight adsorbed 9.25 % with equilibrium time 8.45 min, at 298 K/1 bar) respectively. Both BDA-HCPs can be reused with minor loss in adsorption capacity (2 and 1 %), which makes them excellent candidates to use on industrial scale applications. Adsorption isotherm study (Langmuir, Freundlich, and Temkin) and Kinetics study (pseudo first order and pseudo second order) reveals that this study fit best for Freundlich isotherms and pseudo first order kinetic model for both BDA-HCPs. This research contributes valuable insights into the design of hyper cross-linked materials with high surface area, good pore volume, excellent thermal stability and promising gas adsorption capacities particularly for addressing environmental pollution challenges related to CO2 emissions.